Inflammatory Myofibroblastic Tumor of the Orbit: A Case Series and Literature Review - Guo S; Wang S; Chen C; He X; Yang B; Huang Z; Ma J; Shi J; Jiang L; Chen FK (Journal of Inflammation Research)
Sitong Guo,1,2 Songze Wang,2,3 Chunli Chen,2 Xiaojin He,4 Bentao Yang,5 Zhiqin Huang,2 Jianmin Ma,2 Jitong Shi,2 Libin Jiang,2 Fred Kuanfu Chen6– 8 1Department of Ophthalmology, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People’s Republic of China; 2Beijing Tongren Eye Center, Beijing Tongren Hospital, Capital Medical University; Beijing Ophthalmology and Visual Sciences Key Laboratory, Beijing, 100730, People’s Republic of China; 3Beijing FengTai You’anmen Hospital, Beijing, People’s Republic of China; 4Department of Pathology, Beijing Tongren Hospital, Capital Medical University, Beijing, 100730, People’s Republic of China; 5Department of Radiology, Beijing Tongren Hospital, Capital Medical University, Beijing, 100730, People’s Republic of China; 6Centre for Ophthalmology and Visual Science, The University of Western Australia, Perth, WA, Australia; 7Ophthalmology, Department of Surgery, University of Melbourne, Melbourne, VIC, Australia; 8Department of Ophthalmology, Royal Perth Hospital, Perth, WA, AustraliaCorrespondence: Libin Jiang, Beijing Tongren Eye Center, Beijing Tongren Hospital, Capital Medical University; Beijing Ophthalmology and Visual Sciences Key Laboratory, Beijing, 100730, People’s Republic of China, Email jlbjlb@sina.comPurpose: Orbital inflammatory myofibroblastic tumors (IMTs) are a rare tumor with intermediate biological potential. We analyzed a series of orbital IMTs to determine their unique features.Methods: Records from patients with pathologically confirmed IMT at Beijing Tongren Hospital, Capital Medical University, between January 2004 and August 2022, were reviewed for their ocular presentation and treatment outcomes.Results: Thirteen cases of primary orbital IMT with positive anaplastic lymphoma kinase on fluorescent in situ hybridization were included. These consists of five men and eight women with an age of onset ranged from 2 to 54 years. Nearly half of the primary orbital IMTs displayed local invasion into the maxillary sinus, ethmoid sinus, and pterygopalatine fossa. On magnetic resonance imaging, orbital IMT usually appeared as an ill-defined, oval, irregular, or diffuse mass with heterogeneous signals. Nearly half (46.2%) of these lesions caused bone destruction, and 31% developed recurrence, which was more likely to occur in lesions involving multiple tissues (50%). All cases of recurrence occurred within five months after the first surgery. No patient developed distant metastases.Conclusion: Orbital IMT is rare and prone to local invasion and recurrence. The histology and behavior of orbital IMT requires further investigation.Keywords: inflammatory myofibroblastic tumor, orbit, MRI, pathologic, prognosis